Costs, benefits, and fitness consequences of different migratory strategies - José A. Alves; Tómas G. Gunnarsson; Daniel B. Hayhow; Graham F. Appleton; Peter M. Potts; William J. Sutherland; Jennifer A. Gill (Ecology, 2013)
The relative fitness of individuals across a population can shape distributions and drive population growth rates. Migratory species often winter over large geographic ranges, and individuals in different locations experience very different environmental conditions, including different migration costs, which can potentially create fitness inequalities. Here we used energetics models to quantify the trade‐offs experienced by a migratory shorebird species at locations throughout the nonbreeding range, and the associated consequences for migratory performance, survival, and breeding habitat quality. Individuals experiencing more favorable winter conditions had higher survival rates, arrived on the breeding grounds earlier, and occupied better quality breeding areas, even when migration costs are substantially higher, than individuals from locations where the energy balance on the wintering grounds was less favorable. The energy costs and benefits of occupying different winter locations can therefore create fitness inequalities which can shape the distribution and population‐wide demography of migratory species.